Pemahaman Perpajakan, Sanksi Pajak, Tarif Pajak, Patriotisme, dan Kepatuhan Wajib Pajak Orang Pribadi - Etikasari, Arum Devi; Hidayatulloh, Amir (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
Tax is one of the sources of state revenue, in fact tax is the largest source of state revenue. Thus, studies are still needed related to the factors that encourage taxpayers to comply with paying their taxes. so, to increase insight into the factors that influence taxpayer compliance, researchers conducted a study aimed at analyzing the influence of tax understanding, tax sanctions, tax rates, and patriotism on individual taxpayer compliance. The population of this study were Individual Taxpayers registered at the Tax Service Office throughout Indonesia. The sample of this study was individual taxpayers in Indonesia who had a Taxpayer Identification Number. The sampling technique in the study used convenience sampling. Data were collected by distributing questionnaires with the help of google form. The respondents in this study numbered 151 respondents. The data analysis technique used multiple regression analysis with the help of SPSS. This study obtained results that taxpayer compliance was influenced by tax understanding and tax rates. However, tax sanctions and patriotism did not affect individual taxpayer compliance